An oxide-based heterojunction optoelectronic synaptic device with wideband and rapid response performance. (1st October 2022) - Li, Chunmei; Wang, Jinyong; Li, Dongyang; Ilyas, Nasir; Yang, Zhiqiang; Chen, Kexin; Gu, Peng; Jiang, Xiangdong; Gu, Deen; Liu, Fucai; Jiang, Yadong; Li, Wei
Highlights: The device has a wideband (520∼1550 nm) and high sensitive response to light spike Our device has a rapid response time of 2 ms and presents a stable performance The synaptic device has the functions of color and light source direction recognition Abstract: With the rapid development of science and technology, the emergence of new application scenarios, such as robots, driverless vehicles and smart city, puts forward high requirements for artificial visual systems. Optoelectronic synaptic devices have attracted much attention due to their advantages in sensing, memory and computing integration. In this work, via band structure engineering and heterostructure designing, a heterojunction optoelectronic synaptic device based on Cu doped with n-type SrTiO3 (Cu:STO) film combined with p-type CuAlO2 (CAO) thin film was fabricated. It is found surprisingly that the optoelectronic device based on Cu:STO/CAO p-n heterojunction exhibits a rapid response of 2 ms, and that it has a wideband response from visible to near-infrared (NIR) region. Additionally, a series of important synaptic functions, including excitatory postsynaptic current (EPSC), paired-pulse facilitation (PPF), short-term potentiation (STP) to long-term potentiation (LTP) transition, learning experience behavior and image sharpening, have been successfully simulated on the device. More importantly, the performance of the device remains still stable and reliable after several months which were stored at room temperature and atmospheric pressure. Based on these advantages, the optoelectronic synaptic devices demonstrated here provide great potential in the new generation of artificial visual systems. Abstract : Image, graphical abstract